Single-cell transcriptomics and functional validation revealed PLEKHA5-L as a promoter of growth and migration in brain metastatic melanoma cells - Tang, Xiaogen; Lei, Tingting; Huang, Boya; Wu, Guangjie; Tian, Yizhen; Xiang, Jian; Fu, Dongwei; Zhang, Hongyi (Frontiers in Oncology, 2025)
BackgroundMelanoma brain metastasis is an lethal event. Investigating the molecules that potentially promoted melanoma metastasis is important for targeted therapy.MethodsThe transcriptional profiles of totaling 7 melanoma samples, including 4 primary and 3 brain metastatic tissues were studied on the single-cell RNA sequencing level, and the expression of PLEKHA5 was examined in tumor clusters. Then PLEKHA5 expression was validated in brain Metastatic model by left ventricular injections in nude mice. The functional effect of PLEKHA5 isoforms (Long or Short) on proliferation and migration of melanoma was studied by RNA interference, overexpression by lentivirus vector, CCK8 test, colony formation test, transwell chamber assay. The targets and signal pathways that was potentially regulated by PLEKHA5 was studied by RNA-sequencing.ResultPLEKHA5 expression increased in brain metastatic melanoma at single cell level. PLEKH5 was constantly upregulated in brain metastatic tissue of melanoma in animal model. PLEKHA5-L had the potential for melanoma migration and proliferation by upregulating oncogenes such as HRAS, AKT3 etc. PLEKHA5-L also upregulated expression of PD-L1 and ABC transporters that were associated with therapy resistant.ConclusionPLEKHA5-L was potential therapeutic target for metastatic melanoma.